Relative humidity control and reduction in power consumption via desiccant dehumidification - Ahmed Saleem, Saeed Binghooth; Zainal Alimuddin, Zainal Alauddin, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.